Of Consummation, Matrimonial Promises, Fault, and Parallel Wives: The Role of Original Texts, Interpretation, Ideology and Policy in Pre-and Post-1962 Burmese Case Law - Zan, Myint (Columbia Journal of Asian Law, 2000)
This article is written with four objectives: first, to introduce the evolution of aspects of Burmese law dealing with particular family law issues and their mode of function and operation since colonial times; second, to trace the consequences and changes that were effected in the structure of the Burmese judiciary as well as in aspects of legal thinking and discourse as a result of the 1962 military takeover, in order to relate them to some of the issues that arose in cases decided in the post-1962 era, and to juxtapose and contrast them with other decisions on similar subjects; third, to discern how the concepts of “original texts,” “interpretation,” “ideology,” and “policy” appear intermingled in pre- and post-1962 Burmese case law; and fourth, to illustrate that by analyzing these cases, a reasonable conclusion can be made that legal, political, social and ideological issues cannot always be delineated in the development of Burmese case law.